2015
DOI: 10.1097/tp.0000000000000842
|View full text |Cite
|
Sign up to set email alerts
|

A Rationale for Age-Adapted Immunosuppression in Organ Transplantation

Abstract: Demographic changes are associated with a steady increase of older patients with end-stage organ failure in need for transplantation. As a result, the majority of transplant recipients are currently older >50 years and organs from elderly donors are more frequently utilized. Nevertheless, the benefit of transplantation in older patients is well recognized whereas the most frequent causes of death among older recipients are potentially linked to side effects of their immunosuppressants. Immunosenescence is a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 135 publications
1
88
1
6
Order By: Relevance
“…Moreover, we and others have reported that immunosenescence impacts alloimmune responses following organ transplantation. (29,30) Although rejection rates are less frequent in older patients (13), little is known about age-specific aspects of established immunosuppressants. Yet, age-specific concepts of immunosuppression are of clinical significance as the majority of renal transplant recipients are older than 50 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we and others have reported that immunosenescence impacts alloimmune responses following organ transplantation. (29,30) Although rejection rates are less frequent in older patients (13), little is known about age-specific aspects of established immunosuppressants. Yet, age-specific concepts of immunosuppression are of clinical significance as the majority of renal transplant recipients are older than 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is a novel finding in the debate on age-specific immunosuppression. (29)…”
Section: Discussionmentioning
confidence: 99%
“…There is some clinical evidence that the ageing process is associated with enhanced immunosuppression. For instance, (i) the risk for cancers is enhanced in elderly people, (ii) the efficiency of immunotherapy declines with aging, (iii) transplantation tolerance increases during the aging process, (iv) elderly people are vulnerable to infections, and (v) vaccination efficacy decreases during the aging process [153][154][155]. All these phenomena are associated with increased immunosuppression.…”
Section: Activation Of Immunosuppressive Network With Aging and Alzhementioning
confidence: 99%
“…ATI is a common and well-known feature in various fungal Mendes-Giannini et al 2008;Souto et al 2003), viral (Duan et al 2015;Falkenberg et al 2014;Gao et al 2015) and bacterial infectious diseases (LeyvaRangel et al 2015;Ross et al 2012;Savino 2006). ATI can also be caused by immune suppression (Billard et al 2011;Zhou et al 2016), hunger (Gavia-García et al 2015;Savino et al 2007), chemotherapy, radiography (DeBo et al 2015;Lynch et al 2009), pregnancy (Ekin et al 2016;Jacques et al 2014Jacques et al , 2015, transplant rejection (Gracia-Ahufinger et al 2015;Krenzien et al 2015) and other severe disease conditions (Wang et al 2016). ATI in certain physiological conditions (e.g., during malnutrition and pregnancy) is usually mediated by the neuroendocrine system, and the transient thymic regression is characterized by increased thymocyte death, with the capability to recuperate after the removal of the insult (Gruver and Sempowski 2008;Shanley et al 2009).…”
Section: Introductionmentioning
confidence: 99%